Tinjauan praktik swamedikasi dan konseling obat tanpa resep di Apotek Kecamatan Tempel - Anggraini, Lina; Yuliastuti, Fitriana (Universitas Muhammadiyah Magelang, 2023)
The use of non-prescription drugs in self-medication efforts has been widely used by the public for minor illnesses. Drugs that are often used for self-medication generally fall into the category of non-prescription drugs. People's behavior in self-medication is influenced by the ease of accessing various information about drugs and is also one of the respondents' considerations in selecting drugs. Pharmacists have an obligation to provide correct information regarding the use of non-prescription medicines. This study aims to determine the opinions of pharmacy respondents regarding non-prescription drug counseling and provide an overview of the implementation of self-medication in the Bantul area. A descriptive research design with a direct survey research method with a sample of pharmacies and patients was carried out using a purposive sampling technique. The results of this study show that the three classes of medicines most frequently purchased in the implementation of self-medication are vitamins and supplements (31%), cough and cold medicines (31%), and antipyretic analgesics (25%). Most respondents knew the rules for using drugs (100%), and pharmacists were a factor in selecting drugs (50%). As many as 96% of respondents admitted to reading drug labels when first purchasing. Respondents' opinions regarding counseling showed that there was a large need for non-prescription drug counseling (89%), as many as 61% had received non-prescription drug counseling with a counseling duration of 1–5 minutes.